2002
DOI: 10.1161/01.cir.0000033972.90653.af
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator Inhibitor-1 Promotes Formation of Endothelial Microparticles With Procoagulant Potential

Abstract: Background-Endothelial dysfunction is emerging as a common denominator for diverse and highly prevalent cardiovascular diseases. Increased level of plasminogen activator inhibitor-1 (PAI-1) and procoagulant activity have been recognized as hallmarks of endothelial dysfunction. This study was aimed at investigating cellular actions of PAI-1 and a potential link between PAI-1 and procoagulant state. Methods and Results-Human umbilical vein endothelial cells treated with PAI-1 were subjected to laser confocal flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(107 citation statements)
references
References 32 publications
6
99
0
2
Order By: Relevance
“…Interestingly, the rate of in vitro thrombin generation is accelerated significantly by microparticles obtained from the cultured HUVECs pretreated with PAI-1. 22 However, mast cell-derived exosomes significantly induce PAI-1 expression in endothelial cells and its secretion, providing feedback between the characteristically elevated PAI-1 levels and procoagulant state, both observed in diverse syndromes manifesting as endothelial cell dysfunction. However, because these data were obtained using HMC-1, it remains to be confirmed whether they apply to other human mast cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the rate of in vitro thrombin generation is accelerated significantly by microparticles obtained from the cultured HUVECs pretreated with PAI-1. 22 However, mast cell-derived exosomes significantly induce PAI-1 expression in endothelial cells and its secretion, providing feedback between the characteristically elevated PAI-1 levels and procoagulant state, both observed in diverse syndromes manifesting as endothelial cell dysfunction. However, because these data were obtained using HMC-1, it remains to be confirmed whether they apply to other human mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…22 Factor Xa activity and thrombin generation was monitored by continuous measurement of absorbance at 405 nm. The chromogenic assay was standardized with pure human ␣-thrombin (20 nmol/L).…”
Section: Procoagulant Activity Of Mast Cell-derived Exosomesmentioning
confidence: 99%
“…Elevated plasma level of PAI-1 is considered as a non-traditional risk factor for cardiovascular diseases (Brodsky et al 2002). Rucker et al demonstrated that heat shock stress increases the expression of PAI-1 in vascular tissues of rat muscle (Rucker et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have shown that central obesity correlates with elevated plasma levels of plasminogen activator inhibitor 1 (PAI-1), which has been strongly associated with dysfibrinolysis within the fibrinolytic system, meaning that the balance between normal clot lysis and clot formation is disturbed (Alessi et al, 1997;Bastard et al, 1995;Brodsky, Malinowski, Golightly, Jesty, & Goligorsky, 2002;Vague, Vague, & Cloix, 1971). It is this disturbance in clotting that has led investigators to focus on the plasma levels of PAI-1, which, if abnormally high, lead to both ruptured plaque and thrombotic occlusion.…”
Section: The Mechanism Of Action For the Metabolic Syndromementioning
confidence: 99%
“…It is this disturbance in clotting that has led investigators to focus on the plasma levels of PAI-1, which, if abnormally high, lead to both ruptured plaque and thrombotic occlusion. Ruptured plaque is considered an important mechanism in the development of a myocardial infarction (Brodsky et al;Falk, 1992). Further, elevated plasma PAI-1 levels have been shown to predict infarction and stroke (Juhan- Vague & Alessi, 1996;Juhan-Vague, Morange, & Alessi, 1999).…”
Section: The Mechanism Of Action For the Metabolic Syndromementioning
confidence: 99%